Early Stage of Transition in Central Asian Countries: The Impact of Socio-Cultural Factors - Saidkhon Saidolimov; Mukhtor Nazirov (Periodica Journal, 2022)
This article considers the features of the processes of political transformation during the formation of the foundations of national statehood in the countries of Central Asia. In particular, the article describes the nature of complex internal processes in the states of the region, the influence of sociocultural factors on them, and issues of sustainable development.
Keywords: Uzbekistan; Central Asia; transformation; society